Wage bargaining in an optimal control framework: A dynamic version of the right-to-manage model - Marco Guerrazzi (The Open University, Economics Department, 2007)
This paper aims to represent wage bargaining as an optimal control problem. Specifically, by assuming that employment follows a stock adjustment principle towards the level that maximises profits, i.e., towards labour demand, we build an intertemporal optimising model in which the real wage is continuously set by an infinitely-lived omniscient arbitrator that is called in to resolve the dispute between the workers and the employers. Our theoretical proposal allows to show that unions may speed up the adjustment to equilibrium and it suggests that standard (static) models may understate the distortions implied by wage bargaining.
Keywords: C61; E24; 330; Wage Bargaining; Optimal Control Theory; Right-to-Manage Model; Numerical Solutions; Lohnverhandlungen; Kontrolltheorie; Mathematische Optimierung; Theorie